Binge Eating and Binge-Eating Disorder in Black Women: A Systematic Review - Goode, Rachel W. (Int J Eat Disord, 2020)
OBJECTIVE: Although several effective behavioral treatments for binge-eating disorder (BED) exist, there are racial disparities in treatment access, with African-Americans and/or Black individuals having some of the lowest rates of access to care. Little is known about the experience and treatment of binge eating (BE) and BED among Black women. METHOD: This systematic review, conducted according to PRISMA guidelines, synthesizes information related to BE and BED in Black women. RESULTS: A total of N=38 studies met our eligibility criteria. We did not identify any systematic risk of bias across studies. The majority of included studies used cross-sectional survey methodology, and relied on interview (EDE) and self-report measures (particularly the Binge Eating Scale, BES) for the assessment of BE. Outcomes were inconsistently measured across trials, and there are limited data on the results of evidence-based treatments for BE/BED in Black women. DISCUSSION: Although Black women have similar or higher rates of BE than White women, most research on BE and BED has focused on White women, with Black individuals underrepresented in clinical trials. Future research should examine evidence-based treatments to prevent and treat BED in this population.